Freedom Fighters: An Ecowomanist Reading of the Female Figures in Moses's Life - Dunbar, Ericka Shawndricka (Journal of feminist studies in religion, 2024)
This article underscores how intersectional female collaboration - across ethnicity, age, gender, and class - is supported by the forces of Mother Earth. It posits that the female collective in the book of Exodus both resists the oppressive Pharaonic regime and violence enacted by the deity. It also illuminates that girls and women offer effective models for addressing systemic violence against marginalized and vulnerable people through collective action and wisdom, which shift physical, social, economic, and political realities, enabling life and justice to thrive over killing and oppression.